Consumers’ acceptance towards alcohol-based cosmetic product / Mu’az Zulkifli, Noorul Huda Sahari and Suliah Mohd Aris - Zulkifli, Mu’az; Sahari, Noorul Huda; Mohd Aris, Suliah (Academy of Contemporary Islamic Studies (ACIS), Universiti Teknologi MARA (UiTM), 2024)
Muslim consumers are becoming more affluent and are spending more money on cosmetics and personal goods, which is driving up demand for halal cosmetics. Cosmetics that are clean, pure, and devoid of any haram components are considered to be halal. Alcohol has a purpose of its own and is frequently utilized in industrial goods like cosmetics. Some alcohols from khamr were employed in the manufacturing of cosmetics due to the benefits of alcohol in cosmetic items. Religion-permissible forms of alcohol are still unclear to the general public, notwithstanding fatwas regarding alcohol in cosmetics. This study is to investigate consumers' acceptance of cosmetic goods containing alcohol in light of this interest. Information was gathered from 152 respondents using a survey where questionnaires were distributed to randomly selected respondents among Baling residents in Kedah, Malaysia. The data were analyzed using descriptive analysis via SPSS version 29. The survey focuses basically on two dependent variables, i.e., awareness and acceptance of alcohol-based cosmetic products, and one independent variable. The findings of this study showed that consumers likely accepted the adoption of alcohol in cosmetic products. Most respondents take precautions before purchasing alcohol-based cosmetic products, such as the alcohol content of the product, the types of alcohol used, and the information about the alcohol in the product. Consumers attitudes show a positive attitude before purchasing cosmetic products containing alcohol. Although the consumers attitude toward purchasing alcohol products shows a positive result, their knowledge of alcohol is lower than their attitude toward alcohol-based cosmetics. Thus, it is recommended that an in-depth awareness of alcohol in cosmetic products for consumers is necessary not only for customers in Baling but also throughout the country.